The Role of Accounting in Addressing the National Economic Development - Eduar Baene (Green Publisher Indonesia, 2021)
Along with economic developments in Indonesia, accounting is expected to be able to follow these developments. This is because accounting serves as a provider of information for economic decision making. This study aims to analyze the role of accounting in advancing national economic development. The research method used in this research is descriptive qualitative method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library studies) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. These sources are collected based on discussion and linked from one information to another. Data collection techniques used in this study were observation, interviews and documentation. This data is analyzed and then drawn conclusions. Based on the description analysis above, it can be concluded that the role of accounting in the global economic development of the country cannot be underestimated because it is related to public trust both nationally and internationally. Therefore, accounting has become a profession that is needed in the economic world.